2020
DOI: 10.1200/jco.2020.38.15_suppl.528
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of single-agent adjuvant trastuzumab in older women with early-stage breast cancer.

Abstract: 528 Background: Older adults with multiple comorbidities and poor functional status may not be appropriate candidates for chemotherapy. We conducted a phase II trial to examine the safety and efficacy of single-agent Trastuzumab for older women with early stage Human Epidermal Growth Factor Receptor Type 2 (Her2)-positive breast cancer. Methods: This was a single-arm open label multi-institutional clinical trial of adjuvant single-agent Trastuzumab in women aged ≥ 60 years with stage I-III Her2-positive breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the primary objective of noninferiority for trastuzumab monotherapy was not met, trastuzumab monotherapy demonstrated a favorable 3-year DFS with fewer AEs and a more favorable health-related quality of life. Studies evaluating trastuzumab monotherapy in older populations [18] and/or those with low-grade tumors [19] showed favorable DFS, suggesting that additional assessments of chemotherapy de-escalation strategies, including HER2-targeted therapies only, for the treatment of HER2-positive EBC are warranted to identify candidates who may benefit from a chemotherapy-free regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the primary objective of noninferiority for trastuzumab monotherapy was not met, trastuzumab monotherapy demonstrated a favorable 3-year DFS with fewer AEs and a more favorable health-related quality of life. Studies evaluating trastuzumab monotherapy in older populations [18] and/or those with low-grade tumors [19] showed favorable DFS, suggesting that additional assessments of chemotherapy de-escalation strategies, including HER2-targeted therapies only, for the treatment of HER2-positive EBC are warranted to identify candidates who may benefit from a chemotherapy-free regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Drug exposure was comparable across all chemotherapy subgroups in the safety population, with a planned 18-cycle treatment regimen. The overall median (range) number of cycles was 18 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) for the no chemotherapy subgroups and 18 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) for both chemotherapy subgroups. Multiple events of the same CTC grade were counted only once in that CTC grade.…”
Section: Safetymentioning
confidence: 99%
“…Regarding the safety of trastuzumab in older patients, the results of a large observational study indicated that the risk of cardiac function toxicity was 5.7% [ 18 ] and that it was associated with age [ 18 , 19 ], although it remained manageable [ 18 ], and the risks associated with trastuzumab were outweighed by the benefits [ 18 , 20 ]. A phase II study of trastuzumab monotherapy in older women showed that DFS at 5-year was 86.4% (95% CI: 73.6 to 93.3) with cardiac safety [ 21 ]. In terms of the balance between benefit and harm, we recommend trastuzumab monotherapy if the patients do not receive chemotherapy, based on our current findings.…”
Section: Discussionmentioning
confidence: 99%